Validitas Pengembangan Soal Matematika Model PISA: Konteks Covid-19 Dalam 4 Konten Berbeda - Hafidah Muthiah Azzahra; Yuli Fitrianti Fitrianti; Syutaridho Syutaridho; Arvin Evriani Evriani (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2021)
This study aims to produce valid PISA model math questions in the context of Covid-19. This research is a development research, namely research and development consisting of 2 stages, namely preliminary and formative evaluation stages which include self evaluation, expert reviews, one to one and small group and field test. However, this article only discusses the validity of the questions so that it only reaches the expert reviews and one to one stage. The result of this study is to obtain the validity of the development of the PISA model of mathematical problems in the context of the spread of Covid-19 from expert reviews and from one to one. With the conclusion that the product in the form of questions has been validated based on content, construct and language. An indicator that an instrument is valid is that the expert has received the instrument, both in content and format, without any revision.